NetDDS: A Real-time Interactive Platform Based on the Publish-subscribe Mechanism - Zheng, Pengyi; Rao, Yuan (Recent Advances in Electrical & Electronic Engineering, 2022)
Background: With the continuous development of big data, artificial intelligence, the Internet of things, and blockchain technology, distributed interactive systems have gradually become the mainstream of computing technologies and applications with the help of real-time interaction platforms. The real-time interaction platforms provide a data communication bridge for distributed applications, not only meeting the timeliness and correctness of data interaction but also providing a unified interface for application development. It realizes the plug and play of different functional modules in the distributed system and improves development efficiency for system developers. Objective: According to the characteristics of the large scale, wide range, and complex running environment of distributed interaction systems, this paper analyzes the function and performance requirements of the distributed interactive platform and designs and implements a real-time interactive platform named NetDDS based on a publish-subscribe mechanism. Methods: Concerning the idea of a layered design, the real-time interactive platform is constructed from three aspects: distribution service layer, QoS guarantee layer, and data transmission layer. The platform provides a data synchronization function based on publish/ subscribe mechanism, a configurable QoS guarantee mechanism, and a multi-protocol data transmission mechanism based on Ethernet, ensuring the real-time correctness and reliability of data transmission. Results: Experimental results show that the interactive platform exhibits less delay in message update. Conclusion: This paper proposes a hierarchical architecture, designs and implements a real-time interaction platform based on publish/subscribe mechanism, and provides a topic- based publish/subscribe model to the application layer. The publisher and subscriber directly publish and subscribe with data as the center to meet the real-time requirements of distributed real-time applications.
Keywords: Quality of Service (QoS)